AB1041 Household Ergonomics: Development and Validation of A Novel Tool To Assess Physical Exposures Contributing To Household Work Related Low Back Pain. (15th July 2016) - Ranasinghe, P.D.; Atukorala, I.; Samaranayake, A.; Gunawardana, N.S.
Abstract : Background: Household ergonomic risks-especially physical exposures straining the low back during manual household work can contribute to low back pain in housewives. To date, there are no screening tools to identify physical exposures that cause household work related low back pain. Objectives: To develop and validate "Physical Exposure Check-Household work related low back pain (PEC-HLBP)", a tool to assess physical exposures contributing to household work related low back pain. Methods: Items for PEC-HLBP were generated based on a theoretical framework developed through review of literature, qualitative observations and expert opinion. Item reduction was by a panel of 10 experts based on a scoring system. The draft PEC-HLBP was developed into an interviewer-administered questionnaire with responses in a Likert scale to facilitate responses on the gradient of the physical exposure and the scoring system adopted reflected the gradient of exposure. PEC-HLBP was designed to be answered based on household work activities routinely being performed by the respondent. Exploratory factor analysis using principal component analysis was performed on a sample of 250, 20–50 year old eligible housewives to further reduce items and to assess construct validity. Internal consistency and test retest assessed the reliability. Results: The initial PEC-HLBP contained 36 items. Ten items which scored an average score less than 2 by the panel of experts (score based on the importance as a physical exposure on a 1–5 scale) were eliminated. Exploratory factor analysis of draft PEC-HLBP with 26 items showed 9 factors (Eigen values 1.008–5.163) explaining 64.18% of total variance. All 26 items in draft tool showed factor loadings above 0.4 not requiring further reduction of items. Two factors with items of similar loadings were amalgamated based on the theoretical framework. Finalized PEC-HLBP contained 26 items in eight domains which were assigned names to depict the items they contained (figure 1 ). Experiencing the physical exposures or not were determined based on a predetermined cut off score for each domain. The mean duration to complete the questionnaire was 16 (±4) minutes. Cronbach's Alpha was 0.789 (95% CI 0.725–0.825).The test-retest reliability was good (Spearman`s coefficient above 0.77) for all domains. Response rate among housewives was 83.3% and the response rate for each question was 100% with no missing data. Conclusions: PEC-HLBP is a valid, reliable and acceptable tool to assess physical exposures contributing to household work related low back pain among housewives Acknowledgement: Medical Research Institute, Sri Lanka Disclosure of Interest: None declared